Implementation of Bekasi City Regional Health Insurance Program Implementation Policy - Yuan Sabina, Athiyyah (Pelopor Publikasi Akademika, 2024)
The main problem raised in this study is the ineffectiveness of policies and programs in Bekasi City based on Family Cards and Identity Numbers. Qualitative research strategies combined with descriptive analysis are research methods used by researchers. The expectation that original data could be collected and research subjects could be thoroughly studied to provide the desired findings led to the selection of this methodology and approach. As a result of various factors, including standard factors, policy size and objectives, resources, implementing organization characteristics, implementing attitudes, communication between related organizations and implementation activities, as well as the social, economic, and political environment, the findings of this study can be used to explain why the Bekasi City Health Insurance policy has not been implemented effectively. However, these variables, the characteristic factors of implementing agents and policy resource factors, have not been implemented properly in their implementation, so there are still obstacles in the implementation of the Regional Health Insurance policy. Of course, this is not the best approach to providing quality public services, especially in terms of the Regional Health Insurance Program for People Based on Family Cards and Identity Numbers.